The Influence of Customer Perceived Value on Customer Satisfaction at Yumchi Resto & Catering Harapan Indah, Bekasi - Stefani, Angela; S. Soeprapto, Vishnuvardhana (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Yumchi Resto & Catering Harapan Indah is one of the restaurants in Bekasi that has been able to survive due to the impact of the Covid-19 pandemic, then after the pandemic can maintain and increase its sales up to 2-fold in 2021. This significant increase makes researchers want to research the factors that influence this. The purpose of this writing is to determine the effect of customer perceived value on customer satisfaction at the Yumchi Resto & Catering Harapan Indah restaurant. This study examines the influence of customer perceived value (value that customers feel) seen from the dimensions of emotional value, price value, quality value, social value on customer satisfaction. This study uses quantitative research, namely by distributing questionnaires to find out customer opinions related to the problems studied. The number of respondents in this study were 100 respondents, using purposive sampling method, namely determining the sample based on the criteria or knowledge of the sample taker. Methods of data analysis using simple linear regression with the SPSS program. The results of the study with the t test show that customer perceived value with the emotional value dimension has a positive and insignificant impact on customer satisfaction of 0.799; variable customer perceived value with the dimension of price value has a significant influence on customer satisfaction of 0.045; the customer perceived value variable with the quality value dimension has a negative impact and an insignificant effect on customer satisfaction of 0.601; and the customer perceived value variable with the social value dimension has a positive and insignificant impact on customer satisfaction of 0.739. Based on the results, it was briefly concluded that on the dimensions of Customer Perceived Value which is composed of Price Value, Social Value, Emotional Value, and Quality Value simultaneously or partially, the significance does not have an impact on Yumchi Resto & Catering Harapan Indah customer satisfaction. As for partially, the dimensions of Emotional Value, Quality Value, and Social Value have no significant impact on Yumchi Resto & Catering Harapan Indah customer satisfaction. However, the Price Value dimension has a significant impact on consumer satisfaction at Yumchi Resto & Catering Harapan Indah. This means that customers have a sense of satisfaction from Yumchi Resto & Catering Harapan Indah based on the price value applied. Efforts to increase customer satisfaction at Yumchi Resto & Catering can be carried out based on private values so that consumers can maintain their choice and trust in Yumchi Resto & Catering Harapan Indah, Bekasi and can recommend it to others